IMPACT OF TURKISH MILITARY OPERATIONS ABROAD ON THE FALL OF THE LIRA - Heidernia, Arvin (Revista Gênero e Interdisciplinaridade, 2021)
In this study, the impact of military operations on the exchange rate is estimated. In particular, this study focuses on military operations in Turkey and its impact on the Turkish lira against the pound sterling. Therefore, the aim of the present study is to investigate the impact of Turkish military operations abroad on the fall of the lira. The purpose of this study is analytical-descriptive and theoretical studies. The results of the present study indicate that Turkey has direct, proxy or tension military operations in Libya, Syria, Iraq, Nagorno-Karabakh and Greek waters, which have a negative effect on the country's relations with the European Union and the United States, leading to a fall in value. The Turkish lira.